Non-ionic surfactant vesicles as a carrier system for dermal delivery of (+)-Catechin and their antioxidant effects. (16th March 2021) - Li, Danhui; Martini, Nataly; Liu, Mengyang; Falconer, James R.; Locke, Michelle; Wu, Zimei; Wen, Jingyuan
Abstract: Numerous skin disorders and diseases are related to oxidative stress. The application of an antioxidant, serving as a strong defense agent against oxidation, is of great interest in dermatology yet remains challenging for delivery. This paper aimed to develop a niosome carrier system to deliver the antioxidant (+) Catechin into the skin. (+) Catechin-loaded niosomes were prepared using film hydration technique and the physicochemical properties of drug-loaded niosomes were characterised and investigated by a series of in vitro and ex vivo studies. The optimised formulation displayed an acceptable size in nanoscale (204 nm), high drug entrapment efficiency (49%) and amorphous state of drug in niosomes. It was found that (+) Catechin-loaded niosomes could effectively prolong the drug release. Drug deposition in the viable layers of human skin was significantly enhanced when niosomal carriers were applied ( p < 0.05). Compared to the pure drug, the niosomal formulation had a greater protective effect on the human skin fibroblasts (Fbs). This is consistent with the observation of internalisation of niosomes by Fbs which was concentration-, time- and temperature-dependent, via an energy-dependent process of endocytosis. The research highlighted that niosomes are potential topical carriers for dermal delivery of antioxidants in skin-care and pharmaceutical products.